_t(5t squared t+)
15t2 squared-t-15t+3=15t squared-14t+3
vf=vi+at² simplifying making vi=0, v=at²t²=v/at=√v/atime equals square root of velocity divided by acceleration (or gravity)
No
That's one term. You need at last two to find an LCM. That factors to t(t + 2)(t + 2)
(6x + t)(3x + t)
_t(5t squared t+)
2t
t+t=2tand t*t= t squaredyou would only get t squared if you multiplied
72 = 49.72 + t = 49 + t
15t2 squared-t-15t+3=15t squared-14t+3
v2+36v+99 = (v+3)(v+33) when factored
(3t + 1)(t + 5)
t2+ t - 42 it can't be simplified anymore
49+t
T squared is T times T. T squared and T squared appears to be the addition of T squared with itself. That answer would be 2T squared or 2T^2
t(39.2 - 4.9t)